Performance of an immunochromatography test for vivax malaria in the Amazon region, Brazil - Alberto Ferreira Figueiredo Filho; Maria Cristina Figueredo; José Maria Nascimento; Vanja Suely Pachiano Calvosa; Marinete Marins Póvoa; Ricardo Luiz Dantas Machado
The study was carried out to evaluate the diagnostic performance of the ICT malaria Pf/PvTM test for vivax malaria diagnosis in Belém, Amazon region, Brazil. The results of blood malaria parasites examination using an immunochromatography test were compared with thick blood film (TBF) examination. It was also evaluated the performance of this test storaged at three different temperatures (25°C, 30°C, and 37°C) for 24 hours before use. Overall sensitivity of ICT Pf/PvTM was 61.8% with a specificity of 100%, positive and negative predictive value of 100% and 71.8%, respectively and accuracy of 80.6%. The test sensitivity was independent of the parasite density. This test needs to be further reviewed in order to have better performance for P. vivax malaria diagnosis.